Totally e -continuous functions in ^ ostak’s fuzzy topological spaces - S. Rajakumarl; M. Palanisamy (Utilitas Mathematica, 2025)
The goal of this manuscript, we applied the concepts of e -open & e - closed sets within the context of Sostak’s fuzzy topological spaces. We also developed the notions of r -fuzzy totally e -open sets and r -fuzzy totally e -continuous functions in these spaces, which were used to interpret and explore a new idea of functions is r - ƒ Te -contin. functions. Furthermore, we explored the connections # this new cohort & other established classification of functions in the framework of Sostak’s fuzzy topology.